The influence of branding on consumer buying behaviour: A case of Kinondoni municipality - Mwambusi, Rose Lwitiko (Mzumbe university, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of the degree of Masters of Business Administration in Corporate Management(MBA-CM) of Mzumbe University